2021
DOI: 10.1186/s12974-021-02158-3
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between astrocytes and microglia results in increased degradation of α-synuclein and amyloid-β aggregates

Abstract: Background Alzheimer’s disease (AD) and Parkinson’s disease (PD) are characterized by brain accumulation of aggregated amyloid-beta (Aβ) and alpha-synuclein (αSYN), respectively. In order to develop effective therapies, it is crucial to understand how the Aβ/αSYN aggregates can be cleared. Compelling data indicate that neuroinflammatory cells, including astrocytes and microglia, play a central role in the pathogenesis of AD and PD. However, how the interplay between the two cell types affects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 34 publications
0
89
0
Order By: Relevance
“…In addition to microglia, we found α-syn accumulations in cells negative for CD11b ( Figure 6 C, right side nucleus). Just recently, it has been described that microglia and astrocytes may interact in α-syn clearance, thereby exchanging α-syn among each other ( Rostami et al., 2021 ). Thus, it seems possible that microglia may transfer α-syn to other cell types, e.g., astrocytes, in our OSC experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to microglia, we found α-syn accumulations in cells negative for CD11b ( Figure 6 C, right side nucleus). Just recently, it has been described that microglia and astrocytes may interact in α-syn clearance, thereby exchanging α-syn among each other ( Rostami et al., 2021 ). Thus, it seems possible that microglia may transfer α-syn to other cell types, e.g., astrocytes, in our OSC experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The microenvironment of early AD is characterized by inflammatory responses and oxidative stress, which precede the appearance of the amyloid cascade [ 7 ]. Inflammation is often accompanied by the activation of the immune system, which is ultimately mediated primarily by glial cells, such as microglia and astrocytes [ 58 , 59 ]. Among all non-neuronal CNS cells, microglia are thought to control the metabolic balance in the brain, including the secretion of pro-inflammatory or anti-inflammatory cytokines and phagocytosis of abnormal proteins [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the role of microglia/astrocyte communication in the clearance of protein deposition, human iPSC-derived microglia and astrocytes were co-cultured in the presence of Aβ or α-synuclein (αSYN) fibrils. Firstly, it was observed that microglia and astrocytes in co-culture had a greater ability to clear the protein aggregates compared to single-cell cultures, Rostami et al (2021) . This indicated synergy between the two cell types to provide a better mechanism of clearance.…”
Section: Microglia and Astrocyte Communicationmentioning
confidence: 99%
“…This indicated synergy between the two cell types to provide a better mechanism of clearance. Moreover, live imaging analysis from the co-culture showed the appearance of novel physical structures called nanotubes (tunneling Structures made from cell membranes) keeping the astrocytes and microglia in direct contact for effective communication ( Rostami et al, 2021 ). A previous study conducted by the same group gave evidence that astrocytes were able to link via these structures to other astrocytes ( Rostami et al, 2017 ).…”
Section: Microglia and Astrocyte Communicationmentioning
confidence: 99%